Muslims with Tattoos: The Punk Muslim Community in Indonesia - Mohammad Rokib; Syamsul Sodiq (Al-Jami'ah Research Centre, 2017)
Tattooing is becoming increasingly popular in the predominantly Muslim country of Indonesia. While mainstream society continues to perceive the tattooing practice negatively, many individual Muslims attach positive personal meaning to tattooing. This paper provides some of the academic insights into contemporary perceptions of tattooing among Indonesian Muslims. It focuses on the existence of ‘Punk Muslims’ community whose tattoos form an important part of their cultural identity and on responses to their tattooing practices from the wider society. Data were collected by means of individual interviews, a focus group discussion, and interactive social media communication. This paper reveals that Punk Muslim community has personal meaning of tattoo, while society has different perception. This community considers to maintain their cultural identity as punker symbolized by tattoo and Islam signed by worship.[Tato menjadi semakin populer di negara mayoritas Muslim seperti Indonesia. Ketika sebagian besar masyarakat memandang tato secara negatif, banyak juga Muslim secara pribadi memiliki pendapat positif terhadap tato. Artikel ini menyuguhkan beberapa wawasan akademik atas persepsi kontemporer terhadap tato dalam masyarakat Muslim di Indonesia. Fokus dari artikel ini meliputi eksistensi komunitas Punk Muslim yang menganggap tato telah membentuk bagian sangat penting dari identitas kultural mereka dan juga fokus pada respons dari masyarakat terhadap praktik bertato. Data penelitian dikumpulkan dari interview secara personal, diskusi kelompok terumpun, dan komunikasi interaktif di media sosial. Artikel ini menyatakan bahwa komunitas Punk Muslim memiliki makna personal atas tato ketika masyarakat memiliki penilaian yang berbeda. Komunitas ini mempertimbangkan untuk mempertahamkan identitas kultural sebagai anak punk yang disimbolkan dengan tato dan sebagai orang Islam yang disimbolkan dengan ibadah.]